2014
DOI: 10.1590/1982-021620144513
|View full text |Cite
|
Sign up to set email alerts
|

Satisfação dos usuários do implante coclear com perda auditiva pós-lingual

Abstract: Objetivo avaliar a satisfação dos usuários de Implante Coclear com perda auditiva pós-lingual. Métodos estudo seccional com 51 implantados, pacientes de um centro de referência em saúde auditiva na cidade do Natal-RN. Foram utilizados dois questionários de satisfação adaptados para usuários de implante coclear. Resultados houve um alto índice de satisfação entre os pesquisados, detectado pelo InternationalOutcomeInventory –CochlearImplant(100,0%) e pelo SatisfactionwithAmplification in Daily Life (98,0%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 25 publications
(27 reference statements)
1
10
0
3
Order By: Relevance
“…The use of cochlear implantation (CI) presents a high satisfaction rate among its users (9) and, as reported in other studies, the findings of this survey show that the benefits of this intervention are much more comprehensive than the audiological results in the experience of adults.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The use of cochlear implantation (CI) presents a high satisfaction rate among its users (9) and, as reported in other studies, the findings of this survey show that the benefits of this intervention are much more comprehensive than the audiological results in the experience of adults.…”
Section: Discussionsupporting
confidence: 61%
“…Several studies have assessed the benefit of this intervention, focusing mainly on measuring the gains in speech perception (1)(2)(3)(4)(5) , whereas others have evaluated the impact of CI through the application of quality-of-life (QoL) questionnaires (2)(3)(4)(5)(6)(7)(8)(9)(10) . However, the efficacy of this resource should also be assessed with respect to the subjective aspects of everyday life (11) , using methodologies that enable openset speech perception from the perspective of those who experience this situation, such as Symbolic Interactionism (SI) and Grounded Theory (GT).…”
Section: Introductionmentioning
confidence: 99%
“…The same study showed that subcategorizing satisfaction by positive effects, negative effects, services and costs, and personal image yielded similar optimistic results in all categories except personal image, where little improvement was seen in the adolescents' perception of their social image (de Carvalho et al, 2015). Another study using the SADL questionnaire in a Brazilian cohort of adults with post-lingual hearing loss, found similar results as overall satisfaction with cochlear implantation belied a dissatisfaction with Personal Image and Costs and Services in 13.7 and 27.5% of the population, respectively (Buarque et al, 2014). Approaching patient satisfaction via other tools, particularly the International Classification of Functioning, Disability and Health, Child and Youth version (ICF-CY) and two study-specific questionnaires, a different group of researchers, compared Swedish children with cochlear implants to those with hearing aids.…”
Section: Patient Satisfactionmentioning
confidence: 72%
“…Estudos inseridos nesta revisão (20,23,25,26,33,34,36,37) frisaram que a gratidão pode ser justificada pelo fato de a concessão do AASI não gerar nenhum custo aos usuários, constituindo uma limitação intrínseca às pesquisas que verificam a satisfação de usuários no SUS (49) . Em estudo que avaliou a satisfação dos usuários de implantes cocleares concedidos pelo SUS, também foi encontrada alta satisfação entre os entrevistados (52) .…”
Section: (≥ 18) Sadlunclassified